2013
DOI: 10.1021/es402209w
|View full text |Cite
|
Sign up to set email alerts
|

Changes inArabidopsis thalianaGene Expression in Response to Silver Nanoparticles and Silver Ions

Abstract: The release of silver nanoparticles (AgNPs) in the environment has raised concerns about their effects on living organisms, including plants. In this study, changes in gene expression in Arabidopsis thaliana exposed to polyvinylpyrrolidone-coated AgNPs and silver ions (Ag(+)) were analyzed using Affymetrix expression microarrays. Exposure to 5 mg/L AgNPs (20 nm) for 10 days resulted in upregulation of 286 genes and downregulation of 81 genes by reference to nonexposed plants. Exposure to 5 mg/L Ag(+) for 10 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

14
197
6
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 391 publications
(219 citation statements)
references
References 31 publications
14
197
6
2
Order By: Relevance
“…AgNPs have been implicated in agriculture for improving crops. There are many reports indicating that appropriate concentrations of AgNPs play an important role in enhancing seed germination (Barrena et al, 2009;Shelar and Chavan, 2015), plant growth (Salama, 2012;Sharma et al, 2012;Kaveh et al, 2013;Vannini et al, 2013) and improving photosynthetic quantum efficiency and chlorophyll content (Sharma et al, 2012). AgNPs are also used as antimicrobial agents to manage plant diseases (Lamsal et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…AgNPs have been implicated in agriculture for improving crops. There are many reports indicating that appropriate concentrations of AgNPs play an important role in enhancing seed germination (Barrena et al, 2009;Shelar and Chavan, 2015), plant growth (Salama, 2012;Sharma et al, 2012;Kaveh et al, 2013;Vannini et al, 2013) and improving photosynthetic quantum efficiency and chlorophyll content (Sharma et al, 2012). AgNPs are also used as antimicrobial agents to manage plant diseases (Lamsal et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…AgNPs have been implicated in agriculture for improving crops. There are many reports indicating that appropriate concentrations of AgNPs play an important role in plant growth (Kaveh et al, 2013;Salama, 2012;Sharma et al, 2012;Vannini et al, 2013) and improving photosynthetic quantum efficiency and chlorophyll content (Hatami and Ghorbanpour, 2013;Sharma et al, 2012). AgNPs are also used as antimicrobial agents to manage plant diseases (Lamsal et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported that the plant response to AgNPs results in either enhancement or inhibition of growth depending on AgNP dosage. Of serial concentrations, exposure to specific concentrations of AgNPs could enhance plant growth compared with non-exposed plants, while higher and lower concentrations negatively affect plant growth (Kaveh et al 2013;Qian et al 2013). Of the tested AgNP concentrations (25, 50, 100, 200 and 400 ppm), 50 ppm was the optimal doi: 10.17221/130/2015-CJGPB treatment for eliciting a growth response in Brassica juncea seedlings.…”
mentioning
confidence: 98%
“…Recent studies suggested that AgNPs might be beneficial for enhancement of crops such as common bean, maize, castor, watermelon and zucchini (Salama 2012;Yasur & Rani 2013;Almutairi & Alharbi 2015). There are many reports indicating that the appropriate concentrations of AgNPs have an important role in enhancing seed germination (Barrena et al 2009;Savithramma et al 2012) and plant growth (Sharma et al 2012;Kaveh et al 2013). Agricultural researches have sought to ensure that using nanomaterials in increasing the crop productivity is safe and effective.…”
mentioning
confidence: 99%